2007
DOI: 10.1175/mwr3336.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Hurricane Erin (2001). Part II: Shear and the Organization of Eyewall Vertical Motion

Abstract: A high-resolution numerical simulation of Hurricane Erin (2001) is used to examine the organization of vertical motion in the eyewall and how that organization responds to a large and rapid increase in the environmental vertical wind shear and subsequent decrease in shear. During the early intensification period, prior to the onset of significant shear, the upward motion in the eyewall was concentrated in small-scale convective updrafts that formed in association with regions of concentrated vorticity (herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
63
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 54 publications
21
63
1
Order By: Relevance
“…6, 7). These distribution patterns of vertical motion under the influence of VSW are similar to the results of observation (Marks et al 1992;Black et al 2002) and simulation (Braun and Wu 2007). As simulated by CTRL, the TC circulation contains several scattered areas of concentrated vorticity, with closed circulations in the asymmetric flow field.…”
Section: Analysis With the Virvsupporting
confidence: 85%
See 1 more Smart Citation
“…6, 7). These distribution patterns of vertical motion under the influence of VSW are similar to the results of observation (Marks et al 1992;Black et al 2002) and simulation (Braun and Wu 2007). As simulated by CTRL, the TC circulation contains several scattered areas of concentrated vorticity, with closed circulations in the asymmetric flow field.…”
Section: Analysis With the Virvsupporting
confidence: 85%
“…In contrast to CTRL, REXP2 with strong VSW produces an asymmetric flow across the TC center with considerable mixing of vorticity southwest of TC into the TC center. The asymmetric flow implies that when the shearinduced wavenumber-1 asymmetry becomes large, significant low-level ventilation of the TC circulation (Braun and Wu 2007) occurs (on the southwest of the TC in this study). The vorticity to the east side of the TC circulation increases significantly, suggestive of strong vorticity mixing from the southwestern portion to the TC center, favoring the ultimate intensification of the TC.…”
Section: Analysis With the Virvmentioning
confidence: 72%
“…Wang et al (2004) found resilient TCs for shear values up to 17 ms −1 in a very similar experimental setup. In a simulation of Hurricane Erin by Braun and Wu (2007) the model TC did not decay in a shear environment of 20 ms −1 (the authors noted that the shear in their simulation was greater than in reality). In a simulation of Hurricane Bonnie (Braun et al, 2006), the hurricane intensified in 10-12 ms −1 shear.…”
Section: Intensity Evolution and Storm Resiliencymentioning
confidence: 99%
“…Whether and by which means storms are detrimentally impacted by vertical shear on their periphery has not been well established. In most previous studies of vertical wind shear impacts on tropical cyclones, the ''detrimental'' shear was thought to be that existing over the core (the center and out to some specified radius) of the storm (Marks et al 1992;Franklin et al 1993;Reasor et al 2000;Black et al 2002;Corbosiero andMolinari 2002, 2003;Rogers et al 2003;Chan et al 2004;Braun et al 2006;Braun and Wu 2007;Chen et al 2006) and was often assumed to be horizontally uniform in modeling studies (Jones 1995;Frank andRitchie 1999, 2001;Wong and Chan 2004). For this study, we assume that the presence of an AEJ near the periphery of a storm is not necessarily detrimental to storm development.…”
Section: Vertical Shear and Increased Stabilitymentioning
confidence: 99%
“…They suggested that the SAL negatively impacts tropical cyclones in the following ways: 1) the enhanced low-level temperature inversion, maintained by radiative warming of dust, suppresses deep convective development; 2) vertical wind shear caused by an increase in the lowlevel easterlies associated with the AEJ inhibits tropical cyclone intensification, based upon studies that have shown that shear tends to weaken storms (Gray 1968;Merrill 1988;DeMaria andKaplan 1994, 1999;Frank and Ritchie 2001;Rogers et al 2003;Braun and Wu 2007); and 3) intrusions of dry SAL air into tropical cyclones foster enhanced cold downdrafts (Emanuel 1989;Powell 1990) and lower the convective available potential energy within tropical cyclones. While it was not Dunion and Velden's intention to imply that the SAL's impacts were always negative or were the dominant factor affecting hurricane activity (J.…”
Section: Introductionmentioning
confidence: 99%